Shakespeare and Hospitality Ethics, Politics, and Exchange - Lupton, Julia Reinhard; Goldstein, David (Routledge Studies in Shakespeare, 2016)
This volume focuses on hospitality as a theoretically and historically crucial phenomenon in Shakespeare's work with ramifications for contemporary thought and practice. Drawing a multifaceted picture of Shakespeare's scenes of hospitality-with their numerous scenes of greeting, feeding, entertaining, and sheltering-the collection demonstrates how hospitality provides a compelling frame for the core ethical, political, theological, and ecological questions of Shakespeare's time and our own. By reading Shakespeare's plays in conjunction with contemporary theory as well as early modern texts and objects-including almanacs, recipe books, husbandry manuals, and religious tracts - this book reimagines Shakespeare's playworld as one charged with the risks of hosting (rape and seduction, war and betrayal, enchantment and disenchantment) and the limits of generosity (how much can or should one give the guest, with what attitude or comportment, and under what circumstances?). This substantial volume maps the terrain of Shakespearean hospitality in its rich complexity, demonstrating the importance of historical, rhetorical, and phenomenological approaches to this diverse subject.